2010
DOI: 10.1002/jmri.22347
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐automatic deformable registration of prostate MR images to pathological slices

Abstract: Purpose: To present a semi-automatic deformable registration algorithm for co-registering T2-weighted (T2w) images of the prostate with whole-mount pathological sections of prostatectomy specimens. Materials and Methods:Twenty-four patients underwent 1.5 Tesla (T) endorectal MR imaging before radical prostatectomy with whole-mount step-section pathologic analysis of surgical specimens. For each patient, the T2w imaging containing the largest area of tumor was manually matched with the corresponding pathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…visual approach to correlate in-vivo images with histopathology 2 . A recent study of Mazaheri et al 12 demonstrated how to automate this process with deformable 2D image co-registration. However.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…visual approach to correlate in-vivo images with histopathology 2 . A recent study of Mazaheri et al 12 demonstrated how to automate this process with deformable 2D image co-registration. However.…”
Section: Discussionmentioning
confidence: 99%
“…Mazaheri et al 12 developed a methodology to co-register histology sections with T2W MR acquired using an endorectal coil. This approach used a deformable algorithm and the method of moments, and reported good accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Mazaheri et al. describe a semi-automatic method by using a free-form deformation (FFD) algorithm based on B-splines [125]. This method enabled successful registration of anatomical prostate MR images to pathologic slices.…”
Section: Validationmentioning
confidence: 99%
“…Secondly, we analyzed a single slice rather than the entire gland; the differences observed in that one slice may not preserve a linear relationship with the differences observed should the entire gland had been analyzed. Additionally, while PSMs pursue image registration based on direct anatomical similarity, different strategies using software-based algorithms have been proposed by other groups 2325 and have not been compared to the PSM approach. Although we presented an example of how the cost of the technology has been decreasing, we did not objectively perform a cost analysis of this technique.…”
Section: Discussionmentioning
confidence: 99%